Diabetes and prognosis in a breast cancer cohort - Schrauder, Michael; Fasching, Peter A.; Häberle, Lothar; Lux, Michael P.; Rauh, Claudia; Hein, Alexander; Bayer, Christian M.; Heusinger, Katharina; Hartmann, Arndt; Strehl, Johanna D.; Wachter, David; Schulz-Wendtland, Rüdiger; et al. (Journal of Cancer Research and Clinical Oncology, 2011)
Purpose: Epidemiological studies indicated that type 2 diabetes mellitus may increase breast cancer risk and mortality. The aim of this retrospective cohort study was to examine the effect of diabetes on the clinical course and the prognosis of early stage breast cancer in relation to tumour and patient characteristics. Methods: The cohort analyzed in this study consisted of 4,056 patients with invasive primary breast cancer. We compared overall survival, distant metastasis-free survival and local recurrence free survival between breast cancer patients with and without diabetes. Results: In our cohort 276 breast cancer patients (6.8%) were affected by diabetes compared to 3,780 patients (93.2%) without diabetes. Women with diabetes were significantly older, had larger tumours, and a higher rate of lymph node involvement. After a follow-up period of 5 years, stratification for age and adjustment for other prognostic factors, overall mortality following breast cancer was significantly higher in diabetic breast cancer patients (hazard ratio, HR 1.92; 95% confidence interval, CI 1.49-2.48). We found no significant differences in distant metastasis-free survival and local recurrence free survival between the two groups, but we found a slightly significant higher rate of distant metastasis in the group of patients with diabetes and oestrogen receptor negative tumours (HR 2.28; CI 1.31-3.97). Conclusion: In this study, patients with diabetes and oestrogen receptor negative breast cancer had a more than 2-fold higher risk for distant metastasis compared to patients without diabetes. Diabetes was also associated with an almost 2-fold increase in mortality within the 5 years follow-up period. © 2010 Springer-Verlag.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Breast cancer; Cohort study; Diabetes mellitus; Distant metastasis; Local recurrence; Survival